TRADISI “GUMBREGAN” BUDAYA SELAMATAN KEPADA HEWAN TERNAK OLEH MASYARAKAT DUSUN GERSONO KABUPATEN KARANGANYAR - Rendi Nur Alim Universitas Muhammadiyah Surakarta (Universitas PGRI Adi Buana Surabaya, 2021)
ABSTRACT This article aims to: (1). identify the background of the holding of the Gumbregan tradition, (2). Describe the implementation of the Gumbregan tradition, (3). identify the pros and cons of society related to the Gumbregan tradition. This study used qualitative methods, data collection was carried out by observation and in-depth interviews. The results of this study indicate that the gumbregan tradition is carried out based on the belief of the salvation community that livestock can protect and guard livestock against external disturbances of spirits that can threaten the safety of livestock and this tradition is the teaching of the prophet Solomon in the past which has been carried out for generations. the implementation of the Gumbregan tradition is carried out at wuku gumbreg (Javanese calculation), the sequence of the process starts from eating cows, ngalungi cows, herding cows, invitations. This event is held for one day from morning to evening. Community responses related to the Gumbregan tradition are very diverse, some people are pro with the Gumbregan tradition, some people do not agree or disagree with this Gumbregan tradition. The Gumbregan tradition is still carried out by the people of Gersono Hamlet because it is a symbol of the community's gratitude to the creator who has given all the pleasures and blessings to his people. Keyword: Tradition, Gumbregan, Salvation.